Underpricing Level at Initial Public Offering and Its Factors - Yustisia, Natali; Hilmi, Ahmad (Dinasti International Journal of Digital Business Management, 2025)
This study aims to determine the factors that can affect the level of underpricing of a company's shares when conducting an initial public offering in the period 2018 to 2022. The sample in this study was 161 companies obtained through purposive sampling and the method used was multiple regression analysis using SPSS 26 software. The results found were that underwriter reputation, company size and company age did not affect the level of underpricing of shares. Different results were shown by auditor reputation and return on equity which had a significant negative effect on the level of underpricing of shares. While the debt to equity ratio had a significant positive effect on the level of underpricing of shares. The adjusted R square value of 0.131 indicated that 13.1 percent of the underpricing level was influenced by underwriter reputation, auditor reputation, company size, company age, return on equity and debt to equity ratio.